Enhancing The Competitiveness And Sustainability Of Micro, Small, And Medium Enterprises Through Financial Literacy And Inclusion - Haniati, Martiana; Goso, Goso; Rahmawati, Rahmawati (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to analyze the influence of financial literacy and financial inclusion on the competitiveness and sustainability of MSMEs in Luwu Regency. A quantitative method was applied through a survey of 400 MSME actors and analyzed using multiple linear regression. The findings reveal that financial literacy significantly affects competitiveness but not sustainability. In contrast, financial inclusion significantly influences sustainability but has no significant impact on competitiveness. These results demonstrate the distinct roles of financial literacy and inclusion, suggesting the need for tailored policy interventions to effectively enhance both MSME competitiveness and long-term sustainability based on specific regional and sectoral characteristics.